2019
DOI: 10.1136/bmj.l5016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori treatment and vitamin and garlic supplementation on gastric cancer incidence and mortality: follow-up of a randomized intervention trial

Abstract: Objective To assess the effects of Helicobacter pylori treatment, vitamin supplementation, and garlic supplementation in the prevention of gastric cancer. Design Blinded randomized placebo controlled trial. Setting Linqu County, Shandong province, China. Participants 3365 residents of a high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
173
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 171 publications
(193 citation statements)
references
References 35 publications
5
173
0
1
Order By: Relevance
“…22,[49][50][51][52] Two recent studies from Sweden and Hong Kong suggest that, compared with the background population or matched control individuals, treatment decreases risk of future GAC, but other studies have presented limited and conflicting evidence for which populations would most benefit from treatment of HP. 16,21,33,[53][54][55][56][57][58][59][60] Our study adds to these findings and further suggests that inadequate eradication may explain disparate findings. Our findings that failed eradication is associated with future GAC also lend further credence to the importance of HP in GAC.…”
Section: Discussionmentioning
confidence: 57%
“…22,[49][50][51][52] Two recent studies from Sweden and Hong Kong suggest that, compared with the background population or matched control individuals, treatment decreases risk of future GAC, but other studies have presented limited and conflicting evidence for which populations would most benefit from treatment of HP. 16,21,33,[53][54][55][56][57][58][59][60] Our study adds to these findings and further suggests that inadequate eradication may explain disparate findings. Our findings that failed eradication is associated with future GAC also lend further credence to the importance of HP in GAC.…”
Section: Discussionmentioning
confidence: 57%
“…The incidence (5.7%) of GC, in which gastric adenocarcinoma (GAC) is the dominant subtype, has continued to decline worldwide due to the H pylori treatment [106], but the mortality rate (8.2%) remains the second most common cause of cancer death worldwide (Table 1). As shown in Table 1, the overall genetic alterations of PI3K/AKT pathway are observed with PIK3CA (17%) and PTEN (11%) in GC.…”
Section: Deregulation Of the Pi3k/akt Pathway In Digestive System Tumorsmentioning
confidence: 99%
“…A study reported that daily treatment of 900 mg of Rhus verniciflua Stokes extract decreased the polypoid mass and the flat elevated lesion in an old female patient with gastric adenocarcinoma [123]. Additionally, a randomized intervention trial including 3365 residents revealed that garlic (extract and oil) supplementation could also reduce the mortality of gastric cancer [124]. In a multi-institutional randomized prospective study, combined with clinical medicine tegafur and cisplatin, lentinan could prolong median survival and improve the quality of life in patients with gastric cancer [125].…”
Section: Clinical Trialsmentioning
confidence: 99%